Migration and the Epidemiological Approach: Time and Self-Selection into Foreign Ancestries Matter - Simone Bertoli; Melchior Clerc; Jordan Loper; Èric Roca Fernández (Institute of Labor Economics (IZA), 2024)
Data on individuals of immigrant origin are used in the epidemiological approach in comparative development for understanding cultural persistence, the determinants of cultural norms, and the effects of genetic traits. A widespread presumption is that this approach is exposed to attenuation bias. We describe how the increasing reliance on foreign ancestries to identify respondents' origin can invalidate this presumption. Selfselection into reporting a foreign ancestry and unobserved heterogeneity in the time elapsed since ancestral migration can overestimate the effect of interest. A simple theoretical framework describes the joint influence of these two factors on the estimates obtained from a canonical specification. We provide illustrative examples of the empirical relevance of our concerns drawing on two influential papers in the literature: Fernández and Fogli (2006) and Giuliano and Nunn (2021).
Keywords: F22; O12; Z10; 330; comparative development; migration; ancestry; culture; identity choice